Effect of Zinc Addition in Copper to Structure, Hardness, Corrosion, and Antibacterial Activity - Samura, Lisa; Maulani, Mustamina; Rosyidan, Cahaya; Hartono, Kartika Fajarwati; Prakoso, Suryo; Situmorang, Evi Ulina Margareta; Edbert, Daniel; Soegijono, Bambang; Hasbi, Muhammad Yunan; Susetyo, Ferry Budhi (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Brass (CuZn) is widely used today due to better mechanical, thermal, and chemical properties. The present research fabricated CuZn alloy by adding various Zn (6, 9, and 12 wt.%) to the Cu using gravity casting. Casts CuZn alloy by adding various Zn to the Cu to investigate optimum composition were resulting highest inhibited of bacterial activity. In addition, the structure, hardness, and electrochemical behavior of the alloy were also investigated using XRD, Vickers hardness, and potentiostat equipment. XRD confirmed that CuZn alloy has an alpha phase, and a FCC crystal structure. The rise of the Zn content in the alloy led to an increase in crystallite size, a decrease in the hardness and a shift to a more negative OCP potential at 1200 s measurement. Enhancing the Zn content to 9 wt.% in the alloy lead to decrease the corrosion rate. Moreover, 24-hour post-contact observation found that the sample places removed remained clear of bacteria. The Cu6Zn sample successfully inhibited the growth of Escherichia coli in the 3rd hour, while Staphylococcus aureus was 100 % reduced in the 7th hour. The Cu6Zn sample could be used as an alternative material for medical equipment in ambulances.